Gamma Radiation Hazards and Risks Associated with Wastes from Granite Rock Cutting and Polishing Industries in Egypt - Fares, S.; Ashour, A.; El-Ashry, M.; El-Rahma, M. (Ядерна та радіаційна безпека, 2012)
Geological materials usually contaminated with naturally occurring radioactive
materials (NORM) have become a focus of great attention. The gamma radiation in samples of a
variety of natural tiling rocks (granites) collected from different factories in Egypt for use in the
building industry was measured, employing high-resolution g-ray spectrometry.
In order to assess the radiological impact from the granites investigated. The
radiological hazard indices, annual effective dose equivalent (outdoor and indoor) (Deff), hazard
indices (Hex and Hin), activity utilization indices (Ig, Ia) and excess life time cancer risk (ELCR)
were calculated. The radiological hazard indices for most granite samples are higher than the
internationally recommended values.
Keywords: gamma ray spectrometry; NORM; Radiological risk; Natural radioactivity
Activity concentration of 238U, 226Ra, 232Th and 40K; Absorbed dose rate;Tiling rocks (granites);
Activity utilization index; Granite Waste materials; Energy dispersive X-ray spectrometry (EDS),
XRD. Із застосуванням гамма-спектрометрії високого розділення виміряна потужність
гамма-випромінювання зразків різних природних облицювальних порід (гранітів),
відібраних на різних підприємствах Єгипту і використовуваних у будівельній
промисловості.
Виконано дослідження й аналіз фізичних і хімічних характеристик зразків граніту
для встановлення їх взаємозв’язку з вмістом радіонуклідів.
Ключові слова: гамма-спектрометрія; природна радіоактивність, облицювальні
породи (граніти), коефіцієнт використання активності. С применением гамма-спектрометрии высокого разрешения измерена мощность
гамма-излучения образцов различных природных облицовочных пород (гранитов),
отобранных на различных предприятиях Египта и используемых в строительной
промышленности.
Выполнены исследования и анализ физических и химических характеристик
образцов гранита для установления их взаимосвязи с содержанием радионуклидов.
Ключевые слова: гамма-спектрометрия; естественная радиоактивность,
облицовочные породы (граниты), коэффициент использования активности.